1999
DOI: 10.1037/h0086837
|View full text |Cite
|
Sign up to set email alerts
|

"Getting on with life": Women's experiences and ways of coping with depression.

Abstract: This study explored women's experiences of depression, and in particular how women living in rural communities understand, experience, and cope with feelings of distress unaided by professional help. Participants were 15 women living in rural areas of central New Brunswick who completed a semi-structured interview lasting, on average, 75 minutes. The purpose of the interview was to explore their experiences of depression and their ways of coping with these experiences. The women's accounts were analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 16 publications
4
37
0
Order By: Relevance
“…McIntosh also found that some health visitors dismissed mothers' feelings of depression as normal and self-limiting. Even when depression is not associated with the postpartum period, women tend to attribute symptoms to external circumstances and stress (Scattolon & Stoppard, 1999) or to personal flaws, such as weakness of character (Wrigley, Jackson, Judd, & Komiti, 2005). Normalizing of symptoms can hinder not only care seeking, but also the reporting of symptoms and diagnosis of depression when individuals do seek professional help (Kessler, Lloyd, Lewis, & Pereira, 1999;Parker & Parker, 2003).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…McIntosh also found that some health visitors dismissed mothers' feelings of depression as normal and self-limiting. Even when depression is not associated with the postpartum period, women tend to attribute symptoms to external circumstances and stress (Scattolon & Stoppard, 1999) or to personal flaws, such as weakness of character (Wrigley, Jackson, Judd, & Komiti, 2005). Normalizing of symptoms can hinder not only care seeking, but also the reporting of symptoms and diagnosis of depression when individuals do seek professional help (Kessler, Lloyd, Lewis, & Pereira, 1999;Parker & Parker, 2003).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…(Ussher et al, 2007: 154) In being constructed by her partner as ill, this woman's concerns are regarded as only an indication of individual pathology, and the need for change in her life circumstances is negated. A similar danger is apparent in Scattalon and Stoppard's (1999) research of women's experiences of depression. A number of the women with whom they spoke highlighted the crucial role of poverty on their emotional well-being:…”
Section: The Dominance Of the Dsm At The Expense Of Other Ways Of Knomentioning
confidence: 95%
“…These subject positions are inferiorized through Downloaded by [University of Western Ontario] at 08:58 17 November 2014 a masculine/feminine dualism that defines women as other to, and dependent upon, the masculine norm (Butler, 2004;Irigaray, 1993). Studies have explored women's depression as a loss or crisis of self that is connected to the cultural value and gender positions produced within what Irigaray called a phallocentric economy of desire and affect (Hetherington & Stoppard, 2002;Jack, 1991;Kangas, 2001;Mauthner, 2003;McMullen, 2003;Nicolson, 2003;Rowe, 2004;Scattolon & Stoppard, 1999;Vidler, 2005). From this perspective depression manifests as an effect of the emotional relation to self that is produced through a highly judgemental scrutinizing relation that can rarely be appeased or enable the positive valuing of feminine autonomy.…”
Section: Depression: a Crisis Of Feminine Identitymentioning
confidence: 99%